Strategi Pembelajaran Group Resume Keefetifannya Terhadap Motivasi Belajar Siswa Di SMP - qurota a'yun a'yun (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, 2018)
This research discusses the application of Stratgi Group Resume learning to students' learning motivation at Betara High School 1 in Tanjung Jabung Barat. This research is a quantitative research using Quasi Experiment method with One Group Pretest-posttest Design, data collection is done with motivation questionnaire and student activity observation sheet. The sample in this study were students of class XI IPA 1 taken by cluster random sampling. Judging from the results of the test